Les Étrusques jouaient-ils aux jeux de plateau ? - Edwige Lovergne (Pallas, 2022)
Games as a pastime are rarely represented in Etruria. Based on a few documents with scenes of playful activities, presumed or certain, this article proposes to compare them with the ancient sources and archaeological data. A passage of Book I of Herodotus is the starting point for a reflection on the representation of board games in Etruscan culture.